2011
DOI: 10.1364/oe.19.0a1067
|View full text |Cite
|
Sign up to set email alerts
|

Modal analysis of enhanced absorption in silicon nanowire arrays

Abstract: Abstract:We analyze the absorption of solar radiation by silicon nanowire arrays, which are being considered for photovoltaic applications. These structures have been shown to have enhanced absorption compared with thin films, however the mechanism responsible for this is not understood. Using a new, semi-analytic model, we show that the enhanced absorption can be attributed to a few modes of the array, which couple well to incident light, overlap well with the nanowires, and exhibit strong Fabry-Pérot resonan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
124
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(130 citation statements)
references
References 44 publications
6
124
0
Order By: Relevance
“…The commercial Lumerical FDTD Solutions package is used for the simulations performed in this work. Literature on FDTD simulations of NWs has already shown significant reduction in reflection which is attributed to guided modes, Bloch modes and Fabry-Perot resonances [29][30][31]. Furthermore, it is shown that the geometrical properties of the NW arrays (NWAs) strongly influence the emergence of such modes [13].…”
Section: Simulation Of Reflectance and Power Absorptionmentioning
confidence: 99%
“…The commercial Lumerical FDTD Solutions package is used for the simulations performed in this work. Literature on FDTD simulations of NWs has already shown significant reduction in reflection which is attributed to guided modes, Bloch modes and Fabry-Perot resonances [29][30][31]. Furthermore, it is shown that the geometrical properties of the NW arrays (NWAs) strongly influence the emergence of such modes [13].…”
Section: Simulation Of Reflectance and Power Absorptionmentioning
confidence: 99%
“…For nanowire arrays, mode identification is less straight forward, due to the introduction of periodicity; absorption enhancements in nanowire arrays have been attributed to both leaky waveguide modes of individual nanowires [19][20][21][22] and photonic crystal Bloch modes. 12,[23][24][25][26] Previous reports have examined a wide variety of array dimensions, nanowire geometries, and illumination angles, which also exhibit varying dominant mode resonances.…”
Section: Introductionmentioning
confidence: 99%
“…The array pitch and wire diameter are easily tunable due to the use of patterned masks, created by electron-beam lithography [20] or nanoimprint lithography [22]. Reported light trapping mechanisms include coupling into photonic crystal modes [4,[23][24][25][26], coupling into leaky radial waveguide modes [8,13,15,[27][28][29], and absorption in media considered using effective index models [30,31]. In this paper, we discuss mechanisms for broadband absorption in sparse arrays, where light coupling into localized radial modes dominates over coupling into Bloch-like photonic crystal modes that depend on array periodicity.…”
Section: Introductionmentioning
confidence: 99%